The Comparative Analysis Of Employee Performance Before And After The Provision Of Remuneration At The Ministry Of Religion In North Gorontalo District - Yakup, Yakup; Setiawan, Sasmita Rohizah; Biyangi, Fatra (SENTRALISASI, 2021)
This study aims to examine and analyze differences in employees' performance at the Ministry of Religion, North Gorontalo District, before and after the provision of remuneration. Primary data sources from questionnaires filled out by respondents. The study population consisted of 82 employees determined using the census method. The method employed to answer research problems and test hypotheses are the Analysis of Variance (ANOVA) with the application of Statistical Product Service Solution (SPSS). The results showed that the F-count of the performance score before the provision of remuneration was 2.676 with a significance value of 0.006, while the F-count of the performance score after the provision of remuneration was 3.193 with a significance value of 0.001. These test results indicate a significant increase in performance after the provision of remuneration or performance allowances. Employee performance improvement includes the quality and quantity of work, reliability, accelerated working time, cost savings, quality of service, integrity, work commitment, discipline, and cooperation.Â